Evaluating housing in urban planning using TOPSIS technique: cities of Isfahan province - Izadi, Maliheh; Jafari Vardanjani, Mehdi; Varesi, Hamidreza (Bulletin of Geography. Socio-economic Series, 2021)
The index of housing serves as an important tool in planning for housing so that the parameters affecting housing can be recognized and any planning process is facilitated. Aim. The purpose of the study is to investigate and to evaluate the situation of the housing in cities of Isfahan province. The study is applied and descriptive-analytic in terms of the method. 39 indices were collected in the housing sector. Then the rate of the prosperity and the ranking of the cities were evaluated using TOPSIS method. Prosperity has been defined here as an important index of housing which reflects the welfare of residents. Cities were then categorized into six levels: Very important, Important, Partially important, Moderate, Poor, Very poor in terms of prosperity. Results and conclusions. The results from the study indicate an imbalance in studied indices in the cities, and a clear disparity between the levels of prosperity in the cities, and only the city of Isfahan is in the group of very prosperous with a rate of 0.813.